FROM LEGAL CULTURE TO “ACME” - Kakhvalev, I. (Main Issues Of Pedagogy And Psychology, 2013)
The article represents the significance and priority of legal culture both in the social and individual realization. It reveals all the developmental problems of social and individual consciousness system in the context of legal competence, regarding “ACME” as an integral component.